مستوى العدالة التنظيمية المدركة وأثره على الاندماج الوظيفي: دراسة ميدانية بالمديرية المركزية لامتياز توزيع الكهرباء والغاز بولاية الجلفة "الجزائر" - جوال، محمد السعيد; رابحي، مختار; العقاب، محمد (جامعة عمار ثليجي الأغواط - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
تهدف هذه الدراسة إلى قياس مستوى العدالة التنظيمية المدركة وأثره على الاندماج الوظيفي في المديرية المركزية لامتياز توزيع الكهرباء والغاز بولاية الجلفة، وذلك من خلال دراسة ميدانية باستخدام الاستبانة التي وزعت على عينة عشوائية مشكلة من 75 عامل، وبعد تجميع البيانات وتحليلها باستخدام الأساليب الإحصائية المناسبة توصلنا إلى أن كل من العدالة التنظيمية والاندماج الوظيفي يتحققان بمستويات متوسطة في المؤسسة، بالإضافة إلى وجود أثر ذو دلالة إحصائية لمستوى العدالة التنظيمية المدركة فيها على الاندماج الوظيفي وإن بشكل ضعيف نسبيا، وهذا ما تفسره قيمة معامل التحديد التي بلغت (0.092). وعليه توصي هذه الدراسة المديرية المركزية لامتياز توزيع الكهرباء والغاز بالجلفة بضرورة تعزيز مستويات العدالة التنظيمية السائدة فيها بمختلف مداخلها (التوزيعية، الإجرائية، والتفاعلية) وذلك من أجل ضمان اندماج وظيفي فعال لمواردها البشرية.
The purpose of the present research paper is to measure the level of organizational justice, and the perceived impact on the functional integration at the Central Directorate for Electricity and Gas Distribution of Djelfa (Algeria). The data used in this field study came from a questionnaire survey completed by a random sample of 75 workers of this organization. After data collection, and analyzed using the appropriate statistical methods, both organizational justice and job integration are achieved at medium levels in the organization. There is a significant effect of the perceived level of organizational justice on functional integration in the company with a low level explained by the determination coefficient (r-square value) of 0.092. For better human resources integration, the paper concludes with sets of recommendations for enhancing the levels of existing organizational justice with its various inputs (distributive, procedural, and interactive) in the Central Directorate of Concession for Electricity and Gas Distribution of Djelfa (Algeria).
Keywords: الثقافة التنظيمية -- التمكين الإداري -- إدارة الموارد البشرية -- المؤسسات العامة -- الجزائر